2011
DOI: 10.1186/1755-8166-4-19
|View full text |Cite
|
Sign up to set email alerts
|

A 54 Mb 11qter duplication and 0.9 Mb 1q44 deletion in a child with laryngomalacia and agenesis of corpus callosum

Abstract: BackgroundPartial Trisomy 11q syndrome (or Duplication 11q) has defined clinical features and is documented as a rare syndrome by National Organization of Rare Disorders (NORD). Deletion 1q44 (or Monosomy 1q44) is a well-defined syndrome, but there is controversy about the genes lying in 1q44 region, responsible for agenesis of the corpus callosum. We report a female child with the rare Partial Trisomy 11q syndrome and Deletion 1q44 syndrome. The genomic imbalance in the proband was used for molecular characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…All patients suffered from motor/mental disability except one (Table ). Partial trisomy 11q accompanied by monosomy 12q [Klaassens et al, ] and monosomy 1q44 [Lall et al, ] had usual manifestations such as short neck, upslanting and short palpebral fissures, thin lips, high palate, micrognathia, respiratory distress, ASD, PDA, and hypoplastic nails which were all present in the case reported herein. Additionally the case also has previously unreported features like uplifted ear lobules, inverted nipples, and short halluces.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…All patients suffered from motor/mental disability except one (Table ). Partial trisomy 11q accompanied by monosomy 12q [Klaassens et al, ] and monosomy 1q44 [Lall et al, ] had usual manifestations such as short neck, upslanting and short palpebral fissures, thin lips, high palate, micrognathia, respiratory distress, ASD, PDA, and hypoplastic nails which were all present in the case reported herein. Additionally the case also has previously unreported features like uplifted ear lobules, inverted nipples, and short halluces.…”
Section: Discussionmentioning
confidence: 85%
“…To date, both pure partial trisomy 11q [Greig et al, ; Forsythe et al, ; Pfeiffer and Schutz, ; De Die Smulders and Engelen, ; Delobel et al, ; Zhao et al, ; Yelavarthi and Zunich, ; Partida‐Perez et al, ; Zarate et al, ; Zimberg‐Bossira et al, ] as well as partial trisomy 11q accompanied by other chromosomal anomalies have been reported [Klaassens et al, ; Lall et al, ]. The breakpoint regions in some cases, such as the one reported by Zhao et al [] as 11q13–25, Zarate et al [] as 11q14.1–q21, and Lall et al [] as 11q14–q25 were almost identical to the case reported herein. The clinical abnormalities of trisomy 11q were detailed in 1977 by Francke et al [] who recognized it as “duplication 11(q21/23(qter) syndrome”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caliebe et al [2010] described 2 patients with speech delay, seizures and variable corpus callosum thickness and overlapping deletions in the chromosomal region 1q44, but there was no deletion of AKT3 . ACC appears to be a landmark phenotype for deletion 1q44 syndrome, and the critical genes are proximal to SMYD3 in the 1q44 region, excluding the AKT3 gene [Lall et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 2) [UCSC Genome Browser; Lall et al, 2011]. This gene -not yet considered morbid -is highly expressed in the developing fetal heart.…”
Section: Discussionmentioning
confidence: 99%